Modification of Coconut Grating Machine using ball joint - Maa, Mustaza; Agusto, Dino; Wijianto, Agus; Novison, Roni (Politeknik Caltex Riau, 2024)
Coconut milk is an essential ingredient in daily life. To obtain coconut milk, the coconut flesh must be grated and squeezed from its shell. To enhance the grating process, a coconut grater machine is necessary. However, existing coconut grater machines have been less effective in terms of operational efficiency. Therefore, an idea emerged to improve the efficiency of the coconut grater machine by incorporating a ball-joint mechanism for clamping. This redesigned coconut grater machine utilizes a slider with a ball-joint mechanism on the clamping side, allowing movement along three axes (x, y, and z). This mechanism enables more effective clamping of the coconut shell with shorter clamping time. As a result, the grating capacity increases to 47.01 kg/hour, representing a significant improvement of 1510% compared to the previous coconut grater machine.